Competitive Advantage Management of Madrasah In the Artificial Intelligence Era - Muttaqin, Imron; Tuah, Dilah bin; Zaini, Muhamad; Rianawati, Rianawati; Zurayah, Helva; Suhaimi, Suhaimi (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
Madrasah Aliyah Negeri (MAN) 3 Jombang is one of the high-performing and competitive madrasahs, having been awarded the Research and Skills Madrasah, with a large number of students from pesantren Bahrul Ulum Tambakberas Jombang. This study aims to describe how it plans, implements, and evaluates its competitive advantages. The study uses a descriptive qualitative approach. Data were collected through interviews, observations, and documentation. The data obtained were analysed using thematic analysis. Triangulation and member check are used to enhance trustworthiness. The findings show that MAN 3 Jombang initiated competitive advantage planning through brainstorming, becoming a character-based madrasah, a healthy madrasah, and an Adiwiyata madrasah. This planning involved establishing key strategies, internalising Islamic values, holding work meetings, and setting goals based on the vision, mission, objectives, and strategy. The implementation was carried out by forming working groups, centres for excellence and innovation, extracurricular activities, digitalising services, offering excellent classes and programs, tahfidz, hybrid curriculum, habituation, providing role models, domestic and international partnerships, establishing internal quality assurance, and madrasah culture. Evaluation conducted through academic supervision, Madrasah Self-Evaluation, performance assessment, and product evaluation. This study provides a practical contribution to Islamic education management, especially in madrasas and pesantrens, by applying competitive advantage management grounded in Islamic values to improve quality, achievement, performance, and image branding. This study offers a valuable practical contribution to Islamic education management, particularly for madrasas within pesantren, by emphasising the implementation of competitive advantage management grounded in Islamic values to enhance quality, performance, achievements, and image branding.